Summer in the city - Wilde, Lori; Oliveras, Priscilla; Skilton, Sarah (Kensington Publishing Corp., 2021)
Three connected novellas follow a different woman from a group of NYC friends as they each find love and passion when an unexpected blackout cuts off power to all of Manhattan.